Perfil antropométrico e bioquímico de pacientes renais crônicos de um hospital de referência em hemodiálise em Belém/Pa - ANJOS, Thaynara Santiago dos (2023)
Introduction: Patients with chronic kidney disease on hemodialysis have a high risk of mortality, and protein-energy malnutrition stands out as one of the most common in relation to this condition. In addition, due to renal dysfunction, biochemical changes in chronic renal patients are common such as phosphorus, potassium, calcium and albumin, and early identification of these is very important for nutritional therapy. Objective: To analyze the anthropometric and biochemical profile of chronic renal patients undergoing hemodialysis treatment in a public hospital in Belém - Pará. Methodology: This is a descriptive and analytical cross-sectional study conducted at the Substitute Renal Therapy Service (SRTS) at the Gaspar Vianna Clinics Hospital (GVCH). This study was approved by the Ethics Committee (No. 2,457,835), a total of 58 patients. Data collection was performed from October to November 2018. Results: Regarding nutritional status, according to body mass index and adequacy of arm circumference, 39.7% of the patients were eutrophic and 53.7% were. with some degree of malnutrition, respectively. Regarding serum levels of phosphorus, potassium, calcium and albumin, 51.7% had normal phosphatemia, 60% with normal phosphatemia, 100% with hypocalcemia and 51.7% with hypoalbuminemia, respectively. Conclusion: It is concluded that the study population has malnutrition evidenced by% arm circumference, therefore nutritional monitoring in the study population is essential for the reduction of morbidities, and also dietary monitoring is essential for maintaining biochemical parameters within the appropriate levels.